Giving wasiat more than 1/3 to the wealth / Muhammad Fauzan Ruslan … [et al.] - Ruslan, Muhammad Fauzan; Mahamod, Jalaluddin; Abd Karim, Ahmad Husaini; Sh Abdul Halim, Sh Mohd Ashaari (2023)
According to Imam al-Ghazali and al-Shatibi, wealth and property are one of the de facto needs for the management and conservation of social life. They list life, religion (din), and other things as additional requirements. lineage/progeny (nasab/nasl), soul (nafs), intelligence ('aql), and life (hayyat). Since it is human nature to crave riches, even if just for survival on the one hand and for comfort on the other, the desire to acquire property predates Islam. Islam, however, aims to control that urge. For instance, it is in man's nature to satiate this yearning, and Islam serves us a model for doing so. Islam does not merely value material possessions and riches. as belonging to Allah, but that man is a trustee and they are a trust (Amanah). Adetona claims that it is "a source of test for man like other ephemeral gifts" In this sense, lbn Ahmed writes succinctly: "If we fully understand that wealth is a trust (Amanah) given to us by Allah SWT and Allah is testing us to see how we will discharge the wealth, this would be the stepping stone to us using our wealth in accordance with the commandments of Allah SWT and thereby gaining the everlasting pleasure of Allah and attaining felicity (al-Jannah)."